PERANCANGAN SMART OFFICE MENGGUNAKAN CISCO PACKET TRACER (STUDI KASUS DINAS LINGKUNGAN HIDUP KABUPATEN KUNINGAN) - Fakhru Zaman, Fanji; Rahmat, Hanif (Universitas Islam Al-Ihya Kuningan, 2023)
Smart Office is a concept of an office that optimizes the use of technology to enhance productivity and efficiency. Cisco Packet Tracer is a network simulator used to design, configure, and simulate complex networks. In this research, the author aims to design and implement a network consisting of several network devices such as routers, switches, and servers. Additionally, IoT devices such as Microcontroller Units (MCU), Motion Detectors, and RFID will be added to the research. These devices will be connected to electrical appliances that can be controlled via a computer network using smartphones and computers. The result of this research is a Smart Office prototype that can serve as a reference for the Dinas Lingkungan Hidup of Kuningan Regency in utilizing technology to improve office productivity and efficiency.